Teachers’ Perspective towards Reasons for ‎Reluctance from the Senior Teacher’s Job in the ‎Sultanate of Oman - All-Omairi, Abdulaziz (Jordan Journal of Educational Sciences, 2023)
This study attempts to explore teachers’ perspectives on reasons for reluctance to accept the senior teacher’s job in the Sultanate of Oman. The study followed a descriptive approach based on survey studies and used a questionnaire for data collection. The study sample consisted of 4334 male and female teachers from a number of schools supervised by the Ministry of Education in Oman. The findings showed that reluctance towards the senior teachers’ job is high from the study participants’ perspective. The findings revealed that the reasons related to job duties received the first rank as a key reason for reluctance at a high level, while the material and moral reasons came in second place at a high level. The administrative reasons came in third place, and the personal reasons came in last place, and both of them were at an average level. The qualitative data analysis of participants’ responses to the open-ended question in the questionnaire indicated that there are some other reasons for reluctance towards the senior teachers’ job, such as the negative view towards the senior teachers’ job, workload related to teaching and other duties unrelated to teachers’ specialization, as well as the financial grade required to apply for the job. The study concluded that there are some statistically significant differences in participants’ perspectives about reasons related to reluctance towards the senior teacher’s job in the Sultanate of Oman according to gender and years of experience